The Wire - The Complete Fifth Season Episode 1-10 - Chappelle, Joe; Dickerson, Ernest; Holland, Agnieszka; Fine, Russell Lee; West, Dominic; Doman, John; Faison, Frankie (HBO Video, 2008)
In chronicling a multi-generational family business dealing illegal drugs and the efforts of the Baltimore police to curb their trade, this series draws parallels between these organizations and the men and women on either side of the battle. Drawing similarities between those people who society champion as respectable and law-abiding and those dismissed as thugs, this series sets out to change this viewpoint by showing how criminogenic and unrespectable the articulate, political and respected can be, especially in American political-economic life, and how innocent and decent those from poor, poverty-wracked slums can be. The distinctions between the corporate world and organised crime are shown to have very little relevance. [www.play.com]
Keywords: DVD-Video